PEMBATALAN MEREK YANG TELAH TERDAFTAR BERDASARKAN UNDANG-UNDANG MEREK NOMOR 20 TAHUN 2016 - Hartono, Margareta Kristiani; Suryani, Cendana; Syailendra, Moody Rizqy (UNES Law Review, 2023)
Brand registration is protection in the form of registering the brand itself to the Directorate General of Intellectual Property Rights. Regarding trademark registration, a form of government protection for trademark registration is that a trademark can only be registered based on an application submitted by the trademark owner who is known to be in good faith or according to the principle of good faith. Trademark Cancellation according to Prof. Dr. Rahmi Jened is a procedure taken by one party to search for and eliminate the registration existence of a mark from the General Register of Marks or cancel the validity of rights based on a mark certificate. The purpose of this article is to analyze the protection of registered trademarks against use by other parties. The research method used is Normative Juridical Law method. Law with an analytical-descriptive definition investigates and investigates trademark violations in connection with the brand law number 20 of 2016 and information related to several cases that have been rife. Based on the results of the research, it is concluded that the owner of the trademark rights fulfills the requirements under the trademark and identification law. And those who feel that their brand names are similar are entitled to legal protection from the government. This legal protection can be in the form of preventive legal protection and oppressive reparation. It is necessary to provide evidence to the violators of the brand of violation which later, if proven, will definitely take responsibility for their actions. the responsibility is carried out maybe the trademark is invalid because the trademark violator has an element of bad faith towards the registered trademark and if proven this results in a lot of losses for the trademark that has been registered and furthermore the brand offender must pay compensation.